Health professionals' perception of disrespectful and abusive intrapartum care during facility-based childbirth in LMIC: A qualitative systematic review and thematic synthesis. (2021) - Agyenim-Boateng, Akosua; Cameron, Helen; Bemah Boamah Mensah, Adwoa
Abstract: Background: The interest of the global community in improving women's experiences with childbirth has led to interventions such as facility-based childbirth and the use of skilled birth attendants. However, reports of low facility and skilled birth attendants use continue to exist in literature because of disrespectful and abusive care directed at women during childbirth. The present systematic review examined the question "What are the understanding and justification for disrespect and abuse directed at women by Health Professionals during childbirth or intrapartum care?" Methods: Electronic search was conducted from January 2000 to January 2021 across CINAHL, OVID, PUBMED, PSYINFO databases. The retrieved studies were then filtered through a stringent inclusion and exclusion criteria. Thirteen studies were included in this review; extracted and synthesized using Thomas and Harden's (2008) thematic synthesis method. Results: Three key themes were identified- providers related factors, women related factors, health system related factors. Sub-themes included classification and description, authority and control, reciprocity, providers attitude, rationalization, socio-economic inequalities, lack of assertiveness and inadequate resources. Conclusion: The study demonstrated that HPs were aware and understood the various forms of D&AC. However, they provided justifications such as an act to save mother and baby's life, lack of assertiveness from labouring women and inadequate work resources for their actions. This highlights the need for various stakeholders involved in care during childbirth to reignite commitments to international standards on respectful maternity care and patient safety, such as training of staff and education of women on the process of labour and birth.